Producing the Popular: John Monk Foster and the ‘Industrial Romance’ - Michael Sanders (Cahiers Victoriens et Edouardiens)
This article argues that John Monk Foster’s serialised novel A Pit-Brow Lassie (1889) is an example of the quietist ‘culture of consolation’ which conflates the popular with the commercial and decouples the former from its earlier radical implications. It begins with a brief biographical sketch of Monk Foster and his writing career. It then considers the formal pressures associated with serialised newspaper fiction and the kinds of narrative pleasure generated within those constraints. Next, it argues that the narrative structure of A Pit-Brow Lassie displays an uneven and, at times, uneasy combination of elements derived from a variety of genres, as well as demonstrating many features of the folk tale. The article traces the ways in which these structural elements reduce the interpretative work required of the novel’s readers and also considers the novel’s defence of popular fiction. The article argues that despite its resolutely and recognisably proletarian milieu, class conflict is almost entirely absent from A Pit-Brow Lassie which posits instead a cross-class moral code based on the work ethic. The article concludes by analysing the tensions between the novel’s ‘social mobility’ and ‘marriage/happiness’ plots and argues that Monk Foster has to decouple these plots in order to arrive at an ideologically satisfactory happy ending.